UJI PERSYARATAN ANALISIS STATISTIK - Suryono, Hassan; Rejekiningsih, Triana (Jurnal Inovasi Pendidikan, 2007)
The aim of this research is to find the answer to the following problems: (1) How far can the students understand and apply examination requirements of statistic analysis?; (2) How far can the students understand and apply the statistical analysis in hypothetical examination?; and (3) Is there any significant relationship between understanding and application of examination requirements with statistical analysis in hypothetical examination? The result of the analysis shows that (1) The students' understanding on the application of statistical analysis requirement shows a sufficient result with average of 66.36, standing in classification 60 73; (2) The students' understanding in applying statistical analysis can be stated to be sufficient with average score of 60. 67, so it stands in classification 60 73; and (3) The relationship between students' understanding on the application of examination requirements and students' understanding on the application of statistical analysis has coefficient of correlation of 0,36 with coefficient of determination of 0,131044. It means that the percentage of the influencing factors towards students? understanding on statistical analysis is 13 %, and the percentage of the other influencing factors, that are educational background and the material of Statistic, and Science, is 87%.